(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2021)
Scholars have noted that national culture is heterogeneous (i.e., composed of multiple subcultures) and changes over time. Yet, a system that captures and represents the heterogeneity and change in culture has not been advanced in literature. Attempts have been made to demonstrate the occasion of these important aspects of culture, but none offered a way to capture them in research reporting. Currently, researchers report culture values or cultural dimensions in terms of national scores inadvertently reducing national cultures to monolithic and static phenomena. In this paper, we advance a framework, dubbed the Configured Culture Framework, upon which we relied to propose that: a) the heterogeneity of culture should be captured by reporting the relative standard deviation (or coefficient of variation, rσ) of subcultures within a nation, b) change in culture should be captured by the percent change of the culture per period (%Δ), and c) an average of the subcultures should be used as the country’s culture. The authors were motivated by the diversity of cultures found within each country of the world, a fact, which is most pronounced in Africa.